Bacterial Isolates and Antibacterial Resistance Patterns in a Patient with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Tertiary Teaching Hospital, Southwest Ethiopia - Abdulhakim Mussema; Getenet Beyene; Mulatu Gashaw (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality worldwide. The natural course of COPD is characterized by acute exacerbation. Infectious agents, particularly bacteria, cause exacerbation of COPD in the majority. This study aimed to determine the bacteriology and antibiotic resistance patterns among patients with acute exacerbations of COPD (AECOPD) at Jimma Medical Center. Methods. A cross-sectional study was conducted from March to October 2019. Demographic, clinical, and sputa samples were collected from 39 study participants, who were diagnosed with AECOPD. Bacterial pathogens were identified using standard bacteriological techniques, and anti-microbial susceptibility testing was done by Kirby Bauer’s disk diffusion method. Extended-spectrum β-lactamase (ESβL) and carbapenemase production were confirmed by MASTTM D68C and MASTTM D73C combination disc sets, respectively. Chi-square and odds ratios were calculated. Results. Overall, 69.2% (27/39) of sputum samples were confirmed to be culture-positive. A total of 32 bacterial isolates with 78.1% (25/32) Gram-negative and 21.9% (7/32) Gram-positive bacteria were identified. The predominant bacterial isolates were Pseudomonas aeruginosa 21.9% (7/32), Klebsiella pneumoniae 18.75% (6/32), and Staphylococcus aureus 15.62% (7/32). Overall, 30 (93.8%) of the isolates were multidrug-resistant (MDR). About 48% (12/25) and 8 (32%)of gram negative bacterial isolates were ESBL betalatemase and OXA-48 carbapenemase producers, respectively. Having two or more exacerbation experiences in the previous year were found to be important determinants of the sputum culture positivity. Conclusions. High rates of MDR, ESBL, and carbapenemase producer bacteria were isolated from patients with AECOPD. Empiric antibiotic therapy should consider the prevalence of antibiotic-resistant pathogens and the factor that may increase the occurrence of MDR bacterial pathogens.